Association of high vibration perception threshold with reduced renal function in patients with type 2 diabetes - Zhang, Yongze; Zheng, Biao; Li, Yimei; Shen, Ximei; Huang, Lingning; Zhao, Fengying; Yan, Sunjie (Frontiers in Endocrinology, 2024)
Objective: To investigate the correlation between vibration sensory threshold (VPT) and renal function, including glomerulus and renal tubule, in patients with type 2 diabetes mellitus (T2DM).Methods: A total of 1274 patients with T2DM who were enrolled in the Department of Endocrinology of the First Affiliated Hospital of Fujian Medical University between January 2017 and June 2020 were included. Patients were grouped according to VPT levels and divided into three groups, including the normal VPT group (VPT<15V), the mild-moderate elevated VPT group (VPT15 25V), and the severely elevated VPT group (VPT≥25 V). Linear correlation analysis was used to analyze the correlation between VPT and renal functions, including glomerulus markers urine microalbumin (MA) and urinary immunoglobulin G (U-IgG), and renal tubule marker α1-microglobulin (α1-MG). Chronic kidney disease (CKD) was defined according to Kidney Disease Improving Global Outcomes (KDIGO) criteria. The binary logistic regression of the relation between VPT and CKD, eGFR<60 ml/min, and UACR >30 mg/g were expressed.Results: In the mild-moderate and severely elevated VPT group, injury biomarkers of glomerulus (MA and U-IgG), renal tubule (α1-MG), and the incidence of CKD, eGFR<60 ml/min, and UACR > 30 mg/g were gradually increased compared with the normal VPT group. Furthermore, patients with diabetes and severely elevated VPT had significantly higher levels of MA (β=197.54, p=0.042) and α1-MG (β=11.69, p=0.023) compared to those with normal VPT. Also, patients with mild-moderate elevated VPT demonstrate significantly higher levels of MA (β=229.02, p=0.005). Patients in mild-moderate elevated VPT group (OR=1.463, 95% CI 1.005-2.127; OR=1.816, 95% CI 1.212-2.721) and severely elevated VPT group (OR=1.704, 95% CI 1.113-2.611; OR=2.027, 95% CI 1.248-3.294) are at a higher incidence of CKD and elevated levels of UACR>30mg/g compared to those in the VPT normal group. Moreover, the incidence of positive Upro was notably higher in the severely elevated VPT group (OR=1.738, 95% CI 1.182-2.556). However, this phenomenon was not observed in the incidence of eGFR <60 ml/min.A higher VPT is positively associated with the incidence of CKD in patients with T2DM, particularly with elevated UACR. VPT may serve as a marker for glomerulus and renal tubule injury.